Predictive role of trigeminal ganglion ischemia on scalp survival affected by temporal artery diameters: The first experimental study. Issue 7 (July 2022) - Olgun, Abdulkerim; Sirinoglu, Deniz; Karadag, Mehmet Kursad; Kaya, Zulkuf; Mutlu, Vahit; Kocak, Mehmet Nuri; Demirtas, Rabia; Aydin, Mehmet Dumlu
Summary: Scalp arteries are mainly innervated by trigeminal, facial, and vagal nerves. The ischemic neurodegeneration of the trigeminal ganglion can impede scalp circulation via vasospasm-creating effects. This study was designed to investigate whether there is any link between the vasospasm index of deep temporal arteries and ischemic neuron densities of the trigeminal ganglion after subarachnoid hemorrhage. The study subjects included five normal control rabbits, six sham rabbits, and nine rabbits chosen from a formerly established experimental subarachnoid hemorrhage group created by cisternal homologous blood injection (0.75 mL). These rabbits, all male, were followed up for 3 weeks. The trigeminal ganglion and deep temporal artery vasospasm indexes were examined by stereological methods. Ischemic neuron densities of the trigeminal ganglion and vasospasm index values of deep temporal arteries were compared statistically. Postmortem examinations showed important vasospasms of deep temporal arteries, foramen magnum herniations, and neurodegeneration of the trigeminal ganglion. The mean vasospasm index values and degenerated neuron densities of the trigeminal ganglion were determined as 1.03 ± 0.13 and 10 ± 3/mm 3 ( p > 0.5) in the control group, 1.21 ± 0.18 and 35 ± 9/mm 3 in the sham group ( p < 0.005 for sham vs. control), and 2.54 ± 0.84 and 698 ± 134/mm 3 in the experimental group ( p < 0.0005 for sham vs. control and p < 0.00001 for study vs. control). There was an inverse relationship between the vasospasm index values and the degenerated neuronal density of the trigeminal ganglion. The high degenerated neuron density in the trigeminal ganglion had a facilitative effect on temporal artery vasospasm. Trigeminal ganglion neurodegeneration may promote temporal artery vasospasms after subarachnoid hemorrhage, which has not been previously mentioned in the literature.